e-HRM Strengthens Service Quality in Iraqi Government Banking Sector: e-HRM Memperkuat Kualitas Layanan di Sektor Perbankan Pemerintah Irak - Mahdi, Jwan Fadel; Kadhum, Saadia Haief (Academia Open, 2025)
General Background: The digital era has compelled government institutions, including banks, to adopt innovative technologies to enhance service delivery. Specific Background: Among these innovations, Electronic Human Resource Management (e-HRM) plays a critical role in improving internal efficiency and customer satisfaction. Knowledge Gap: Despite its growing global relevance, empirical studies on the impact of e-HRM on service quality in Iraqi government banks remain limited. Aims: This study investigates the relationship between e-HRM implementation and the quality of banking services at the Iraqi Bank of Commerce, Rasheed Bank, Rafidain Bank, and Nahrin Islamic Bank. Results: The findings reveal that e-HRM significantly contributes to service quality through improved employee performance, accuracy, administrative efficiency, and customer satisfaction. Electronic training programs, streamlined HR functions, and reduced processing time emerged as key enablers. Novelty: This study offers a focused analysis within the Iraqi public banking sector, diverging from general approaches by directly connecting e-HRM functions to measurable service outcomes. Implications: The results suggest that adopting modern HR technologies and fostering a digital transformation culture can enhance banking competitiveness and customer trust, providing a strategic advantage for public financial institutions in developing economies. Highlights: e-HRM improves efficiency, accuracy, and service quality. Focus on Iraqi government banks’ digital HR adoption. Recommends training and tech investment for better services. Keywords: e-HRM, service quality, government banks, digital transformation, employee performance